Specific persistent symptoms of COVID-19 and associations with reinfection: a community-based survey study in southern China - Liu, Dongjing; Chen, Binglin; Liao, Xuejiao; Zhang, Zheng; Wei, Sen; Han, Xinxin; Xu, Yong (Frontiers in Public Health, 2024)
Background: This study aimed to investigate the incidence of COVID-19 persistent symptoms among previously infected Chinese community residents and explore associations of specific COVID-19 persistent symptoms with reinfection and other factors. Methods: A community-based survey was conducted in a southern city of China from August 3 to 24, 2023. Face-to-face questionnaires were distributed to a total of 1,485 residents to collect their information. Multivariable logistic regression analysis was used to examine the association between specific persistent symptoms and reinfection of COVID-19, along with age, gender, and educational level. Results: Of the 1,485 participants, 1,089 (73.3%) reported they had been infected with COVID-19. Among them, 89.1% reported having ongoing persistent symptoms and 14.2% reported had two or more times of infection. Fatigue, cough, and headaches were the top 3 symptoms being reported. Participants with reinfection were associated with a higher probability of reporting headaches (OR:1.54, 95 % CI:1.06-2.25), loss of or change in smell and/or taste (OR: 1.90, 95% CI: 1.27-2.83). Participants aged 45 and above and who had a bachelor's or higher degree were more likely to report chest tightness or shortness of breath, impaired sleep, and brain fog. Discussion: During the post-emergency period of COVID-19 pandemic, the incidence of ongoing persistent symptoms among Chinese residents remains high. Individuals whose initial infection was longer than 1 year have the highest probability of reporting having multiple symptoms. Reinfection may increase the risk of reporting headaches, loss of or change in smell and/or taste, impaired sleep, and brain fog.